Quality of Life for Adult Patients with Chronic Obstructive Pulmonary Disease - Hamzah, Maryam; Mansour, Khalida (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): To determine the quality of life for adults with a chronic obstructive pulmonary disease. Methodology: A descriptive study was carried out on (80) patients with a chronic obstructive pulmonary disease from December 2008 through October 2009 with special inclusion criteria (adult paƟents from 18 years and above exclude the patients who suffer complication related of disease and from psychological problems and other chronic illnesses. The data were analyzed through the application of descriptive data analysis approach and inferential data approach. Result: The study indicated that the determination of QoL for COPD depended on the level of effect .The grades according to R.S are: "high" effect of disease in the physical, level of independence and environmental domain and "moderate" in the psychological domain, social domain and "low" in the spiritual domain. Finally the study revealed that there is significant association between (types of smoking, occupation after disease, family history) with total score QOL and no significance with sex, age, marital status, educational level, income. Recommendation: The study recommended that the establishment of pulmonary rehabilitation centers for chronic obstructive pulmonary disease, an educational programs and manual guide should be distributed to the chronic obstructive pulmonary disease patients.